Performance and microbial communities of a batch anaerobic reactor treating liquid and high-solid sludge at thermophilic conditions. Issue 101 (19th October 2016) - Zhang, Dongling; Yuan, Haiping; Yu, Bao; Dai, Xiaohu; Huang, Xiaoting; Lou, Ziyang; Zhu, Nanwen
Abstract : HS-AD with TS of 20% achieved similar reactor utilization efficiency as that in L-AD, and enriched hydrogenotrophic methanogens Methanoculleus . Abstract : To investigate the balance between volumetric methane production and substrate loading on anaerobic digestion (AD), long-term batch experiments were conducted at different total solids (TS) contents of 5% (R1), 10% (R2), 15% (R3) and 20% (R4), respectively. The results showed that maximum cumulative methane production (233 mL gVS −1 ) and VS removal efficiency (48.49%) was achieved in R1. Volatile fatty acids (VFAs) accumulation in R4 was 57.2% higher than that in R2 and 5.69 times higher than that in R1. Glucose degradation rate (GDR) for R3 and R4 declined fast indicating lower microbial activities than those in other two reactors. Microbial community analysis revealed that Coprothermobacter for proteins degradation and Methanosarcina for methanogenesis were enriched in R1 with relative abundance of 25.0% and 34.5%, respectively. Hydrogenotrophic methanogens was dominant in treatment of high-solid AD, in accordance with VFA accumulation. The assessment of methane production performance showed similar reactor utilization efficiency between R1 and R4.